8x-3=2(x+15)

Simple and best practice solution for 8x-3=2(x+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3=2(x+15) equation:


Simplifying
8x + -3 = 2(x + 15)

Reorder the terms:
-3 + 8x = 2(x + 15)

Reorder the terms:
-3 + 8x = 2(15 + x)
-3 + 8x = (15 * 2 + x * 2)
-3 + 8x = (30 + 2x)

Solving
-3 + 8x = 30 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-3 + 8x + -2x = 30 + 2x + -2x

Combine like terms: 8x + -2x = 6x
-3 + 6x = 30 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + 6x = 30 + 0
-3 + 6x = 30

Add '3' to each side of the equation.
-3 + 3 + 6x = 30 + 3

Combine like terms: -3 + 3 = 0
0 + 6x = 30 + 3
6x = 30 + 3

Combine like terms: 30 + 3 = 33
6x = 33

Divide each side by '6'.
x = 5.5

Simplifying
x = 5.5

See similar equations:

| 1/10(x+3)=1/4(2-x) | | 4m-3+7m=30 | | 2(x-5)+3=11 | | x+0.8=0.4(x+5) | | 10+2x=50 | | (7x+9)=(6+10x) | | 4x+1.3=6x-1.1 | | 2x-72+x-15=11 | | 2a^2-3a+5=0 | | 2x-1080=2x-11 | | 4(x-4)+2x=6(x+5)-46 | | 8(x-3)=4 | | x-9=-3x-9 | | 2x-72+x-15=2x-11 | | -7(x-4)=21 | | x-15=2x-72 | | 10-2x=50 | | x/4+4/5=5/12 | | 7x-3+3x=9 | | 5(x+7)=4(x-6)+x | | 7x-3+9=3x | | 7x-3=3x | | 6(-7)+x=7(x-7)+7 | | 2x+11=19-2x | | 20(x+3)=4(15+5x) | | 2x-5/8+x=2x+5/2+2 | | -3(2m-9)+7(m-4)=12-9 | | x/2-4=2 | | -6x-x=0 | | x^4-3x^2-10= | | -2(x+3)=18 | | 56p^2+15p-56=0 |

Equations solver categories